Dampak Deep-Fat Frying Berulang terhadap Degradasi Minyak dan Transformasi Mutu Organoleptik Singkong Goreng - Nur Ariyani Agustina; Dian Rosalina (Jurnal Pertanian Khairun, 2025)
This study aims to evaluate the effects of repeated cassava frying using the deep-fat frying method at 180°C on the physicochemical and sensory quality of Red Palm Oil and Palm Oil. The experiment employed a two-factor Completely Randomized Design (CRD) consisting of five frying repetitions and two types of oil. The analytical parameters assessed included peroxide value, moisture content, free fatty acid (FFA) content, impurity level, and organoleptic attributes (taste, texture, aroma, and color). The findings demonstrated that repeated frying exerted a significant influence (p < 0.05) on both oils, particularly in terms of moisture content, FFA concentration, and peroxide value. Sensory evaluation indicated that cassava fried in Red Palm Oil consistently achieved higher scores for texture, aroma, and color compared to that fried in Palm Oil. Moreover, the interaction between oil type and frying frequency showed a statistically significant effect on the measured parameters. Red Palm Oil exhibited superior oxidative stability relative to Palm Oil and maintained favorable sensory characteristics up to the second frying cycle. Based on these results, it can be concluded that using oil more than two to three times during deep-fat frying markedly decreases oil quality and may compromise the sensory attributes of the resulting fried products.